Demographic regimes and social reproduction of labour - Bagchi, Amiya Kumar (2004)
In analysing demographic outcomes, not only must the conventionally differentiated demand and supply factors be kept in mind, but also the interaction of those factors and the way they are shaped by social and political forces. In order to understand the specifics of demographic behaviour in particular historical contexts, it is necessary to distinguish between several different aspects of population growth and its development or deterioration in terms of morbidity and mortality. This paper attempts to adduce some historical evidence suggesting the diversity of demographic regimes and its bearing on issues of economic and human development. - Reproduced.
Keywords: Labour